Physio@Home: Design explorations to support movement guidance - TANG, Richard (Institutional Knowledge at Singapore Management University, 2014)
Patients typically undergo physiotherapy with the help of a physiotherapist who teaches, guides, and corrects the patients as they perform exercises. It would be nice if people could repeat these exercises at home, potentially improving their recovery rate. However, without guidance and/or corrective feedback from a physiotherapist, the patient will not know whether they are doing their exercises correctly. To address this problem, we implemented a prototype that guides patients through pre-recorded exercise movements using visual guides overlaid atop a mirror-view of the patient on a wall-mounted display. We conducted informal evaluations and pilot studies to assess our prototype and identified some working designs and design characteristics. Collected data will assist us in developing future iterations of the system and designing improved guides for physiotherapy sessions at home.